All-optical cascaded ion acceleration in segmented tubes driven by multiple independent laser pulses. (25th September 2019) - He, H; Qiao, B; Shen, X F; Yao, W P; Yao, Y L; Zhou, C T; He, X T; Zhu, S P; Pei, W B; Fu, S Z
Abstract: A scheme to achieve all-optical cascaded ion acceleration driven by intense laser pulses is proposed, where a series of segmented tubes are used. First, the high-flux ion beam is produced via collisionless shock acceleration in the first tube segment driven by an intense picosecond laser, and then undergoes successive post-accelerations in a cascaded manner via magnetic vortex acceleration driven by low-power terawatt-femtosecond lasers when it propagates through each subsequent tube segment into the vacuum gaps between them. By controlling the delay of the femtosecond lasers as well as the vacuum gap between the tube segments, not only the maximum energy of the ion beam can be boosted, but also its energy spectrum can be tuned to be quasi-monoenergetic. Two-dimensional particle-in-cell simulations show that the maximum energy of the primary proton beam, produced by the picosecond laser at intensity 8.8 × 10 19 W cm −2, can be boosted from 123 to 181 MeV with only two post-accelerations by using 100 fs lasers at the same intensities.